2004
DOI: 10.1016/s1044-5005(04)00016-2
|View full text |Cite
|
Sign up to set email alerts
|

Management control systems and strategy change in buyouts

Abstract: The impact of management buy-outs (MBO) on strategy and management control systems (MCS) is little understood. Previous research by Jones (1992) focused on efficiency-enhancing buy-outs that were a feature of the early development of the market. However, MBOs are heterogeneous and more recent developments have involved ownership changes that stimulate entrepreneurial practices. The novel contribution of this paper is to use Simons' (1995) classification of beliefs systems, boundary systems, diagnostic and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
(36 reference statements)
0
16
0
13
Order By: Relevance
“…However, despite the assertions of Simons and others (for example Flamholtz, 1983) that core values will create shared perspectives among actors, who are seen as passive (Gray, 1990, Tessier andOtley, 2012), there is little empirical evidence to suggest how they do this or whether this can be achieved. Because research typically examines core values that are already in place, little is known about how a core value travels through time and space, influencing the actions of organisational actors (Bruining et al, 2004, Mundy, 2010, Tuomela, 2005, Widener, 2007. Nixon and Burns (2005, p. 264) note that: "One point that appears to emerge from the empirical reality […] is that either the management control literature has over-emphasised the influence of diagnostic and interactive controls relative to informal, social controls (the belief and boundary systems of Simons (1995) framework), or the social controls are becoming more important in the 21st century.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, despite the assertions of Simons and others (for example Flamholtz, 1983) that core values will create shared perspectives among actors, who are seen as passive (Gray, 1990, Tessier andOtley, 2012), there is little empirical evidence to suggest how they do this or whether this can be achieved. Because research typically examines core values that are already in place, little is known about how a core value travels through time and space, influencing the actions of organisational actors (Bruining et al, 2004, Mundy, 2010, Tuomela, 2005, Widener, 2007. Nixon and Burns (2005, p. 264) note that: "One point that appears to emerge from the empirical reality […] is that either the management control literature has over-emphasised the influence of diagnostic and interactive controls relative to informal, social controls (the belief and boundary systems of Simons (1995) framework), or the social controls are becoming more important in the 21st century.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to protect public funds, strict requirements have to be fulfilled before public funding can be received; it differs from private funding, as for receiving public funding, the required controls need to be installed ahead, whereas for private funding controls are often implemented during the financing process. In addition, private investees are rather interested in long-term controls, for example venture capitalists require financial budgets (Bruining et al 2004), or operating and cash budgets (Davila and Foster 2005) to be installed on a regular basis whereas for public, generally non-equity, funding 'only' cost projections or process steps of the respective project have to be provided. It became clear that public funding is an important issue in R&D projects which are frequently recipients of considerable amounts of such funds.…”
Section: Contingency Factors: Innovation Related Characteristicsmentioning
confidence: 99%
“…It has been shown that venture capitalists use their power over their investee's management in order to influence the type of information they receive, its quality and frequency (Sweeting 1991;Mitchell et al 1995;Wright and Robbie 1996). Furthermore it has been reported that VC financing is positively related to the use of financial budgets (Bruining et al 2004), operating and cash budgets (Davila and Foster 2005) and more frequent reporting (Robbie et al 1997;Bruining et al 2004). It is therefore hypothesised that,…”
Section: Venture Capital and Categories Of Mcssmentioning
confidence: 99%
“…Eisenhardt (1985Eisenhardt ( , 1989 berpendapat bahwa sistem imbalan berbasis hasil akan dapat meningkatkan sikap terhadap risiko dibandingkan sistem imbalan berbasis perilaku. Penggunaan pengukuran kinerja secara diagnostik untuk meningkatkan sikap terhadap risiko sesuai dengan pendapat Abernethy dan Brownell (1999) serta Bruining et al (2004) yang menyatakan bahwa secara tradisional, sistem pengendalian memiliki peranan diagnostik melalui proses penilaian dan pemberian penghargaan atas kinerja manajer. Dengan demikian dapat diperkirakan bahwa semakin tinggi penggunaan sistem pengukuran kinerja secara diagnostik akan meningkatkan sikap bank Islam terhadap risiko.…”
Section: Landasan Landasan Landasan Landasan Landasan T T T T Teori Eunclassified